Tess of the d'urbervilles - Hardy, Thomas (Penguin London, 2002)
Cruelly seduced by her relative, the cynical Alec D'Urberville, betrayed by the moral Angel Clare and haunted by her guilt and shame, Tess becomes Hardy's indictment of all the crimes and hyprocrisies of 19th century England. Young Tess Durbeyfield attempts to restore her family's fortunes by claiming their connection with the aristocratic d'Urbervilles. But Alec d'Urberville is a rich wastrel who seduces her and makes her life miserable. When she meets Angel Clare, she is offered true love and happiness, but her past catches up with her and she faces an agonizing moral choice. This unique critical text is taken from the Clarendon edition, based on the manuscript and collated with Hardy's later revisions